Cell death is involved in sexual dimorphism during preimplantation development - Oliveira, C. S.; Saraiva, N. Z.; Lima, M. R. de [UNESP]; Oliveira, L. Z.; Serapiao, R. V.; Garcia, J. M. [UNESP]; Borges, C. A. V.; Camargo, L. S. A. (Elsevier B.V., 2016)
In bovine preimplantation development, female embryos progress at lower rates and originate smaller blastocysts than male counterparts. Although sex-specific gene expression patterns are reported, when and how sex dimorphism is established is not clear. Differences among female and male early development can be useful for human assisted reproductive medicine, when X-linked disorders risk is detected, and for genetic breeding programs, especially in dairy cattle, which requires female animals for milk production. The aim of this study was to characterize the development of female and male embryos, attempting to identify sex effects during preimplantation development and the role of cell death in this process. Using sex-sorted semen from three different bulls for fertilization, we compared kinetics of bovine sex-specific embryos in six time points, and cell death was assessed in viable embryos. For kinetics analysis, we detected an increased population of female embryos arrested at 48 and 120 h.p.i., suggesting this time points as delicate stages of development for female embryos that should be considered for testing improvement strategies for assisted reproductive technologies. Assessing viable embryos quality, we found 144 h.p.i. is the first time point when viable embryos are phenotypically distinct: cell number is decreased, and apoptosis and cell fragmentation are increased in female embryos at this stage. These new results lead us to propose that sex dimorphism in viable embryos is established during morula-blastocyst transition, and cell death is involved in this process. (C) 2016 Elsevier Ireland Ltd. All rights reserved.
Keywords: Sexual dimorphism; Preimplantation development; Female embryo; Apoptosis; Caspase 3